2018
DOI: 10.1103/physrevlett.120.171101
|View full text |Cite
|
Sign up to set email alerts
|

Scalar Hairy Black Holes in Four Dimensions are Unstable

Abstract: We present a numerical analysis of the stability properties of the black holes with scalar hair constructed by Herdeiro and Radu. We prove the existence of a novel gauge where the scalar field perturbations decouple from the metric perturbations, and analyze the resulting quasinormal mode spectrum. We find unstable modes with characteristic growth rates which for uniformly small hair are almost identical to those of a massive scalar field on a fixed Kerr background.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 47 publications
(67 reference statements)
2
38
0
Order By: Relevance
“…It is worth to point out that it is difficult to numerical analysis the stability properties of rotating multistate boson stars. However, a good way to guarantee the stability of a specific solution is to have the linear perturbation mode in [39].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth to point out that it is difficult to numerical analysis the stability properties of rotating multistate boson stars. However, a good way to guarantee the stability of a specific solution is to have the linear perturbation mode in [39].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, Frolov et al [35] (henceforth FKKS), have found an ansatz, based on the conformal Killing-Yano 2-form, which separates the Proca quasi-normal mode equations on the Kerr-NUT-(A)dS family of spacetimes. We use this approach here, in which finding the spectrum of Proca modes reduces to solving two decoupled, differential eigenvalue problems, to systematically cover the parameter space of superradiantly bility [15,22,23], though these will still be unstable to higher m superradiant modes [24]. unstable modes.…”
Section: Introductionmentioning
confidence: 99%
“…The uniqueness theorem [30][31][32][33][34][35][36] tells us that curved spacetime described by Kerr-Newman(KN) metric in the Einstein-Maxwell gravitational theory can hold at most three global conserved quantities, which are named as mass, electric charge and angular momentum. Correspondingly, no-hair conjecture [19,25,[37][38][39][40][41][42] for black holes states that static matter field (such as the massless scalar field) perturbations of the black hole in KN family can not be permanently hold.…”
Section: Introductionmentioning
confidence: 99%